2023
DOI: 10.12911/22998993/168614
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Quality Status, Nutrients, and Phytoplankton Communities in the Coastal Zone of East Aceh Regency, Indonesia

Abstract: Due to rapid urban development in the coastal area of the East Aceh Regency, water quality degradation and marine pollution issues become the primary concern in this region. Moreover, seasonal observation of water quality and phytoplankton has yet to be assessed. This study aimed to determine the control of seasonal water quality and nutrients over phytoplankton abundance throughout the East Aceh coast. Direct field measurements and laboratory analyses were performed to collect the primary data, whereby the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Except for station 2 (Lapoipoi), the ammonia concentration was below the allowed standard (less than 0.3 mg/ L). The ammonia concentration indicates that the N fixation and ammonification process takes place very well in the Sembilan Archipelago, which is very useful for supporting autotroph biota in photosynthesis (Tjahjo et al, 2023).…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 95%
See 4 more Smart Citations
“…Except for station 2 (Lapoipoi), the ammonia concentration was below the allowed standard (less than 0.3 mg/ L). The ammonia concentration indicates that the N fixation and ammonification process takes place very well in the Sembilan Archipelago, which is very useful for supporting autotroph biota in photosynthesis (Tjahjo et al, 2023).…”
Section: Fisheries and Aquatic Sciencesmentioning
confidence: 95%
“…The water temperature salinity in the study area ranged from 30℃−32℃ and 31‰−34‰, respectively, with the highest value observed at Batanglampe station. The relatively higher temperature in the study area could impact the surrounding ecosystem, such as increasing heavy metals and nutrient deposition in water (Tjahjo et al, 2023;Wisha et al, 2018).…”
Section: Water Quality Data and Status In The Sembilan Archipelagomentioning
confidence: 99%
See 3 more Smart Citations